Determinants of Banks' Profitability and its Implication on Risk Management Practices: Panel Evidence from the UK in the Period 1999-2006 - Li, Yuqi (2007)
This study investigates the impact bank's specific factors and macroeconomic factors on bank's profitability, which is measured by return on average assets (ROAA) in the UK banking industry over the period 1999-2006 with aim to indicate the strengthen of risk management in banks. The results show that the impact of loan loss reserves has a negative impact on profit and statistically significant. This implies that higher credit risks result in lower profits. The result for liquidity is mixed and not significant, indicates that conclusion about the impact of liquidity remains questionable and further research is needed. Capital strength was one of the main determinants of UK banks performance providing support to the argument that well capitalized banks face lower costs of going bankrupt, which reduces their cost of funding. Finally, we observe macroeconomic variables, that inflation, interest rate and GDPGR have insignificant impact on performance. The prove of the importance of internal factors provide further implication on the strength of risk management practice in banks.